2009
DOI: 10.1111/j.1600-0633.2008.00334.x
|View full text |Cite
|
Sign up to set email alerts
|

Eradication of the invasive Pseudorasbora parva results in increased growth and production of native fishes

Abstract: –  The topmouth gudgeon, Pseudorasbora parva, has been described as Europe’s most invasive fish. To control their UK invasion, some lentic populations at risk of causing fluvial dispersal have been eradicated. The first of these operations was from a lake in north‐west UK in March 2005 using rotenone application; prior to eradication, their mean density was estimated as 6.1 m−2 whereas since eradication, no P. parva have been recorded. Prior to rotenone application, the majority of native fishes were removed, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 23 publications
0
21
1
1
Order By: Relevance
“…Bitterling were not used for the diet overlap assessment because their major diet items were non-animal food such as detritus and phytoplankton, which are common food for this species (Przybylski, 1996;Koutrakis et al, 2003) and are not supposed to be limiting in the reservoir. In contrast to this study, much higher overlaps of trophic niches were observed between topmouth gudgeon and roach (48−73%) and between topmouth gudgeon and rudd (86−92%) in small ponds in UK in a study based on stable isotope analysis (Jackson and Britton, 2013) and high diet overlaps result in the depressed somatic growth of roach (Britton et al, 2009). Rosecchi et al (1993) reported that the diet of topmouth gudgeon was very similar to that of other littoral native fish species in Lake Mikri Prespa, Greece.…”
Section: Discussioncontrasting
confidence: 77%
“…Bitterling were not used for the diet overlap assessment because their major diet items were non-animal food such as detritus and phytoplankton, which are common food for this species (Przybylski, 1996;Koutrakis et al, 2003) and are not supposed to be limiting in the reservoir. In contrast to this study, much higher overlaps of trophic niches were observed between topmouth gudgeon and roach (48−73%) and between topmouth gudgeon and rudd (86−92%) in small ponds in UK in a study based on stable isotope analysis (Jackson and Britton, 2013) and high diet overlaps result in the depressed somatic growth of roach (Britton et al, 2009). Rosecchi et al (1993) reported that the diet of topmouth gudgeon was very similar to that of other littoral native fish species in Lake Mikri Prespa, Greece.…”
Section: Discussioncontrasting
confidence: 77%
“…While numerous studies have been conducted concerning the impacts of piscivorous fish invasions on fish communities and receiving ecosystems (e.g., Goudswaard et al 2008;Copp et al 2009), study on impacts of planktivorous fish introduction have been remarkably limited (e.g., Brooks and Dodson 1965;McCrary et al 2007;Britton et al 2009). Results of our study demonstrate that introduction of N. taihuensis might induce reduced growth and reproductive investment of H. leucisculus, and could consequently influence later recruitment to the spawning stock.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the eradication of introduced fishes is also viewed by many as a controversial and almost impossible goal due to its high expense and difficulty of success (Myers et al , 1998; Simberloff, 2002; Britton et al , 2008). Although eradication has been used effectively against populations of invasive species, the chance of success is usually directly proportional to the spatial extent of dispersal (Culver & Kuris, 2000; Anderson, 2005; Rayner & Creese, 2006), with eradication of fishes most effective in relatively small, closed, sparsely vegetated water bodies, particularly when rotenone is used (Lozano‐Vilano et al , 2006; Britton et al , 2009).…”
Section: Management: Remediation and Mitigationmentioning
confidence: 99%